Validation of a Patient-Completed Caprini Risk Score for Venous Thromboembolism Risk Assessment - H. E. Fuentes; L. H. Paz; A. Al-Ogaili; X. A. Andrade; D. M. Oramas; J. P. Salazar-Adum; L. Diaz-Quintero; C. Acob; A. Tafur; J. Caprini (TH Open, 2017)
Abstract